Indicators for tracking Climate Smart Investment Plans (CSAIPs) in Africa - Njuguna, Lucy; Nowak, Andreea C. (2024)
This dataset provides examples of indicators that are relevant for assessing progress in the implementation of adaptation components of the Climate Smart Investment Plans (CSAIPs). The development of the indicators draws on the elements prioritized in the CSAIPs. This was accomplished by using the impact pathways generated from the CSAIPs as the basis for developing indicators in addition to document review. The document also includes a case for Morocco, where indicators specific to conservation agriculture are outlined and characterized. Metodology:Document review